Cochlear implantation and residual hearing preservation long-term follow-up of the first consecutively operated patients using the round window approach in Uppsala, Sweden. (2nd September 2020) - Schart-Morén, Nadine; Erixon, Elsa; Li, Hao; Rask-Andersen, Helge
Abstract : Objective: We conducted a long-term follow-up study to investigate the time course of residual hearing in our first 21 consecutively operated cochlear implant (CI) patients using the round window (RW) approach . The study may provide additional information about the influence of a flexible lateral wall electrode array on cochlear function. Methods: Data were available for long-term follow-up (>5 years) in 15 patients. Pure tone audiometry (PTA) was assessed at 0.125–8 kHz preoperatively, and at one, three and >5 years postoperatively. Insertion angle, number of electrodes inside the cochlea, user-time of the processor and stimulation strategy were documented. Results: Twelve out of 15 patients had residual hearing after a follow-up period of five years (mean 86 months, range: 61–103 months). Four out of 15 patients had >75% complete hearing preservation (HP), 8 out of 15 had 25–75% partial HP and 3 out of 15 patients had complete loss of hearing. There was a high correlation between insertion angle and HP. Conclusion: Long-term HP was possible in 12 out of 15 cases. Even patients with complete hearing loss at long-term follow-up showed high performance in speech understanding and were full-time users.